Multi-Period Stochastic Dominance - Levy, Haim; Paroush, Jacob (Management Science, 1974)
First degree stochastic dominance rules for uncertain options (distributions of returns) have been developed for the following two cases: (a) multi-period additive utility functions, (b) univariate utility functions and compound distributions of returns. In the first case, the suggested rule is a necessary and sufficient criterion for efficiency analysis, while in the second case we provide only sufficiency conditions for dominance. For the univariate case an efficient set of portfolios can be constructed for investment groups that differ in their investment horizon. Where returns over time are independent, the longer the investment horizon the smaller the efficient set. However, the relationship between the size of the efficient set and the investment horizon is not simple when interdependence of returns is allowed.